Life, Science, and Power in History and Philosophy. Issue 1 (1st March 2019) - Suzuki, Akihito; Takabayashi, Akinobu
Abstract: Osamu Kanamori (1954–2016) was a prolific author of science and technology studies in Japan in the late twentieth and early twenty-first centuries. He represented many new directions, which he originally learned from France, the United States, and Japan. He influenced histories of scientific ideas and STS in Japan and East Asia. Around the same period, a new history of medicine in modern Japan started to take off. Many historical studies of modern medicine in Japan are published in English. This special issue tries to examine the relationship between Kanamori's works and Japanese medical historians and medical sociologists. After extensively reviewing and summarizing the variety of themes and genres within the works of Kanamori, these four papers will discuss four topics of medical technology, infectious diseases, psychiatric war pensions, and bioethical sci-fi works which have all been inspired by the works of Kanamori. This special issue explores the extensive works of Kanamori and the new history of medicine in Japan and argues that the new history of medicine in the near future becomes a core academic discipline within the relationship of the philosophical discussion of medicine in society and culture.